2009
DOI: 10.1074/mcp.m900188-mcp200
|View full text |Cite
|
Sign up to set email alerts
|

In Planta Proteomics and Proteogenomics of the Biotrophic Barley Fungal Pathogen Blumeria graminis f. sp. hordei>

Abstract: To further our understanding of powdery mildew biology during infection, we undertook a systematic shotgun proteomics analysis of the obligate biotroph Blumeria graminis f. sp. hordei at different stages of development in the host. Moreover we used a proteogenomics approach to feed information into the annotation of the newly sequenced genome. We analyzed and compared the proteomes from three stages of development representing different functions during the plant-dependent vegetative life cycle of this fungus.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
79
2
6

Year Published

2011
2011
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 78 publications
(88 citation statements)
references
References 29 publications
1
79
2
6
Order By: Relevance
“…These candidate secreted effector proteins (CSEP) differ from previously identified B. graminis avirulence proteins AVR A10 and AVR K1 , which do not contain a predicted signal peptide (Ridout et al 2006;Sacristán et al 2009). The CSEP superfamily includes many of the genes and proteins previously identified as specifically expressed in haustoria ) and in infected epidermis (Bindschedler et al 2009(Bindschedler et al , 2011. One member of this superfamily, CSEP0055, has recently been shown to reduce HI when silenced by HIGS and interacts with barley pathogenesis-related protein PR17c and is, therefore, an experimentally validated effector (Zhang et al 2012).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…These candidate secreted effector proteins (CSEP) differ from previously identified B. graminis avirulence proteins AVR A10 and AVR K1 , which do not contain a predicted signal peptide (Ridout et al 2006;Sacristán et al 2009). The CSEP superfamily includes many of the genes and proteins previously identified as specifically expressed in haustoria ) and in infected epidermis (Bindschedler et al 2009(Bindschedler et al , 2011. One member of this superfamily, CSEP0055, has recently been shown to reduce HI when silenced by HIGS and interacts with barley pathogenesis-related protein PR17c and is, therefore, an experimentally validated effector (Zhang et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…These genes encode proteins we had previously identified as abundant in infected tissues (Bindschedler et al 2009(Bindschedler et al , 2011 and which showed the greatest levels of differential transcript accumulation in infection structures (Spanu et al 2010).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Some of them share a Y/F/WxC motif in the N-terminal part of the mature protein (Bindschedler et al, 2009(Bindschedler et al, , 2011Godfrey et al, 2010;Spanu et al, 2010;Pedersen et al, 2012). Only a few CSEPs have been studied and shown to play a role in virulence.…”
mentioning
confidence: 99%